Business Networks and entry modes : the case of Entry in Poland - Soares, Eleonore Amélia Queiroz (2017)
This Masters Final Assignment has the following purposes: (1) to review the assumptions of business network theory and entry modes, (2) to examine how these concepts can interfere in an industrial inter-firm relationship, and (3) to illustrate such insights with a case documented during an internship in KG International. This study attempts to explain why some firms, even after a failure in the process to enter a foreign country, do not give up or replace that target country with another.